Could serum total cortisol level at admission predict mortality due to coronavirus disease 2019 in the intensive care unit? A prospective study - Güven, Mehmet; Gültekin, Hamza (São Paulo Medical Journal, 2021)
BACKGROUND: Critical diseases usually cause hypercortisolemia via activation of the hypothalamic-pituitary-adrenal axis. OBJECTIVES: To investigate the relationship between serum total cortisol level and mortality among coronavirus disease 2019 (COVID-19) patients in the intensive care unit (ICU), at the time of their admission. DESIGN AND SETTING: Prospective study developed in a pandemic hospital in the city of Şırnak, Turkey. METHODS: We compared the serum total cortisol levels of 285 patients (141 COVID-19-negative patients and 144 COVID-19-positive patients) followed up in the ICU. RESULTS: The median cortisol level of COVID-19-positive patients was higher than that of COVID-19 negative patients (21.84 μg/dl versus 16.47 μg/dl; P < 0.001). In multivariate logistic regression analysis, mortality was associated with higher cortisol level (odds ratio: 1.20; 95% confidence interval: 1.08-1.35; P = 0.001). The cortisol cutoff point was 31 μg/dl (855 nmol/l) for predicting mortality among COVID-19-positive patients (area under the curve 0.932; sensitivity 59%; and specificity 95%). Among the COVID-19 positive patients with cortisol level ≤ 31 μg/dl (79%; 114 patients), the median survival was higher than among those with cortisol level > 31 μg/dl (21%; 30 patients) (32 days versus 19 days; log-rank test P < 0.001). CONCLUSION: Very high cortisol levels are associated with severe illness and increased risk of death, among COVID-19 patients in the ICU.